Irving Fisher (1867-1947) in Retrospect - Barber, William J. (American Economic Review, 1997)
Anniversaries inspire retrospective reflections. In turn, retrospective reflections frequently generate scholarly publications. I should like to comment briefly on scholarly enterprises recognizing Irving Fisher at three moments in time. Though each is different, each throws significant light on aspects of Fisher's prolific career as well as on the nature of our discipline. The first anniversary benchmark dates from 1937 and marks Fisher's 70th birthday. This took the form of Festschrift entitled The Lessons of Monetary Experience. The 14 contributors, as editor Arthur D. Gayer explained, were aware of the wide range of topics to which Fisher had made original contributions. They had decided, however, that it would be most useful to structure the Festschrift around a single topic of leading importance. In the environment of 1937, the salience of monetary issues was not in doubt. Fisher himself-with his persistent calls for reflation, then stabilization of the general price level-was in the thick of contemporary debate on these matters. So also were the contributors, whose ranks included Marriner S. Eccles, John H. Williams, Alvin H. Hansen, James Harvey Rogers, R. G. Hawtrey, and John Maynard Keynes. The essayists, it will be noted, were not all like-minded. Though they shared high regard for Fisher's contributions to the discipline, few of them were in complete accord with Fisher. The purpose of this anniversary exercise was to stimulate and sharpen professional understanding of problems of first importance to the nation's economic health. In view of the priority he attached to solutions underpinned by scientific findings, Fisher was obviously comfortable with this approach, even though it meant that many of his other career achievements went unattended. A tribute to Fisher of quite different sort appeared in 1967 on the occasion of the 100th anniversary of his birth. All but one of the essays then appearing in volume entitled Ten Economic Studies in the Tradition of Irving Fisher (William Fellner et al., 1967) were written by members of the Yale economics department. (The exception was centennial appreciation prepared by Paul Samuelson.) The resulting publication was organized on the following principle: authors were to select topic to which Fisher had made an original contribution and to extend the analysis he had offered to embrace the state of the art in the mid-1960's. The broad sweep of Fisher's inventiveness as contributor to the economist's tool kit was on display here. For example, Fellner took note of Fisher's contribution to utility theory and his attempts to devise statistical method to measure marginal utility; Marc Nerlove addressed distributed lags, Fisherian innovation; Richard Ruggles used Fisher's work on the making of index numbers as point of departure; Herbert Scarf examined general-equilibrium modeling with attention to its Fisherian roots; James Tobin took note of the relation between Fisher's theories of saving and interest and more recent work on life-cycle saving and balanced growth; Henry C. Wallich examined contemporary controversies over monetary theory and policy against the backdrop of Fisher's restatement and amplification of the quantity theory. The 100th-birthday volume bore ample testimony to the continuing vitality of Fisher's analytic style in professional discourse. The contrast with the agenda set for the 70thbirthday Festschrift, it will be noted, could not have been more striking. The earlier publication focused on single topic of immediate relevance to policy, to the exclusion of all else. The later publication captured multiple dimensions of Fisher's professional pioneering, with emphasis on his innovations as theorist. These volumes reflected priorities of the profession at the time they were produced. * Department of Economics, Wesleyan University, Middletown, CT 06459-0024.